Review of the impact of urban parks and green spaces on residence prices in the environmental health context - Chen, Kaida; Lin, Huimin; You, Shuying; Han, Yan (Frontiers in Public Health, 2022)
Urban parks have consistently played an important role in people's living environment, reflecting house prices and the extent of the people's attention. Although many studies have been conducted in this filed, the consolidated related research has not been discussed often. Therefore, related papers on the impact of urban park green spaces on housing prices in recent years should be sorted out. Different choices of urban parks and green areas will undoubtedly influence research methods, housing preferences and the nature of the effects. Consequently, a logical framework of previous studies must be constructed. This study will review the literature from four aspects: (i) review of research methods on how park green spaces affect home prices (i.e., Research techniques, such as hedonic price analysis methods, geographically weighted regression models and neural network models, are frequently used in studies, and methodological advancements have helped the field advance); (ii) examining the varying effects of the same or similar types of parkland on home values; (iii) review of studies on the subject, analyzing variations in the scope and degree of the effects of various parks on home values in terms of such factors as park size, accessibility and serving size and (iv) review of innovative research perspectives, translating the issue of impact of parklands on housing prices into a study of the capitalization and amenity of parklands.